Respiratory pathogens in infants and young children with acute respiratory illness: a prospective cohort study, China, 2023–2024 - Yuqing Li; Mingwei Wei; Mingwei Wei; Lunbiao Cui; Xiang Huo; Lisha Ma; Ran Tao; Tao Wu; Suyang Qi; Baolong Wang; Xiuyun Shi; Yuanbao Liu; et al. (Frontiers in Public Health, 2025)
BackgroundInfants are vulnerable to acute respiratory infections (ARIs), which result in pediatric morbidity and even fatalities. A surge of ARIs among infants and young children was reported in China in 2023, garnering global attention. We aimed to investigate the frequency and types of respiratory pathogens associated with the risk of acute respiratory illnesses in infants and young children during this period.MethodsWe established a cohort of 2-month-old healthy infants across three counties in Suqian City, Jiangsu Province, China. The infants in the cohort donated throat swabs at enrollment and then underwent a follow-up for active monitoring of common ARIs. Throat swabs collected from infants experiencing common ARIs were analyzed for respiratory pathogens using targeted next-generation sequencing (tNGS).ResultsBetween 7 February and 17 April 2023, a total of 804 infants were invited to participate. Among them, 796 participants were enrolled (423 [53.1%] male, 373 [46.9%] female) with a median age of 71.0 days. Frequently detected respiratory pathogen carriers at baseline included Staphylococcus aureus (S. aureus) (17.9%), Cytomegalovirus (CMV) (16.0%), and Acinetobacter baumannii (A. baumannii) (15.3%). In the follow-up period up to 30 April 2024, 1,412 episodes of common ARIs were recorded (164.5 per 100 person-years). A total of 675 specimens were collected during the episodes of common ARIs and qualified for analysis, of which 636 (94.2%) had at least one positive detection of respiratory pathogens, with the most frequently detected pathogens being CMV (43.7%), A. baumannii (35.6%), and Rhinovirus (HRV) (29.3%). Among the pathogens, human adenovirus (HAdV) and human respiratory syncytial virus (RSV) (18, 36.0%) were the most common pathogens detected among 50 hospitalized cases of ARIs.ConclusionOur data provide a better understanding of epidemiological patterns of respiratory pathogens in infants and young children from 2023 to 2024. CMV, A. baumannii, and HRV were the most commonly detected pathogens in common ARI cases, while HAdV and RSV were more frequently observed in hospitalized cases with ARIs. These findings suggest that shifts in the pathogen spectrum are closely linked to disease severity, highlighting the need for targeted prevention and control strategies.